Association Between the Child Opportunity Index and Individual Level Social Risks - Florinda Islamovic, MD, MS; Samantha Levano, MPH; Hemen Muleta, MD; Jonathan M. Gabbay, MD; Marina Reznik, MD, MS; Kevin Fiori, MD, MS (Journal of Pediatrics: Clinical Practice)
Objective: Area-level indices, including the Child Opportunity Index (COI), are used as proxies for individual Health Related Social Needs (HRSNs). There is increasing literature suggesting limitations of these indices. There is no literature evaluating the relationship between the COI and HRSN in the pediatric population. Our objective is to assess the relationships between the COI 2.0 and 3.0 with individual-level HRSNs among pediatric patients. Study design: Cross-sectional study of pediatric patients screened for HRSN between November 2022 and December 2023 at a large academic hospital in the Bronx, New York. Multivariate logistic regression models were used to assess the association between the COI tertiles and HRSNs. The predictive ability of COI in identifying HRSNs was also calculated. Results: A total of 17,760 children with HRSNs and geographic identifiers were included in the analysis with 16% reporting at least one HRSN and approximately 90% living in the low COI areas. In adjusted models, national normalized COI 3.0 showed significantly higher odds of HRSNs in moderate (OR 1.57 CI: 1.06, 2.31) and low opportunity (OR 2.34 CI: 1.64, 3.35) areas compared to high opportunity areas. State normalized COI 3.0 showed higher odds of reporting HRSNs in low opportunity areas only (OR: 1.87 CI: 1.08, 3.27). There was no significant association between HRSNs and COI 2.0 nor the Metropolitan normalized COI 3.0. Conclusions: The COI provides context in which individuals live, however, it is a poor proxy for individual HRSNs. Improvements were seen from COI 2.0 to 3.0, highlighting that continued updates to indices are important.